Enhancing the design and utilization of asthma action plans through community-based participatory research in an urban African American community. Issue 2 (February 2021) - Kakar, Rishtya; Combs, Ryan; Ali, Nida; Muvuka, Baraka; Porter, Jennifer
Highlights: Community partnership developed an enhanced childhood asthma patient education tool. All recruited providers used new tool and majority preferred it to previous forms. Asthma medication images improved patient-provider communication. Culturally-informed books are good incentives for study participation. Abstract: Background: Across the U.S., large inequities in asthma prevalence and outcomes persist, disproportionately affecting low-income, minoritized children. West Louisville is particularly impacted by these inequities due to a complex interplay of socioeconomic, historical, and industrial processes. Additionally, low health literacy and mistrust in healthcare exacerbate poor asthma self-management. Objective: To engage community members and health professionals to address childhood asthma management in a marginalized community experiencing significant health inequities. Patient Involvement: Although prior asthma knowledge was not required, the majority of our community advisory council (CAC) members either had asthma or cared for children/grandchildren with asthma. Through facilitated decision-making using the Boot Camp Translation approach, the CAC chose to focus on improving asthma self-management in their community through enhancing the design and utilization of asthma action plans (AAPs). Methods: Upon adding inhaler images to a user-friendly AAP, the CAC developed and implemented a provider incentive program and a health communication campaign to promote the Tool's utilization. Evaluation of the intervention consisted of a short questionnaire measuring relevant patient demographics and campaign knowledge, and phone interviews with providers to gather feedback on the incentive and Tool design. Results: Over the short two-month intervention, a total of 8 practices with 28 providers used 153 Tools to provide asthma self-management counseling. The majority of providers preferred the enhanced Tool to other AAPs they had used. Inhaler images facilitating improved communication regarding asthma medications. Discussion: Using a participatory approach, a community preferred intervention targeting barriers to effective asthma control increased provider utilization and community awareness of AAPs and bridged a communication gap between patients and providers. Practical Value: Leveraging community members' (including patients/caregivers) and health professionals' expertise led to the development of an enhanced patient-education tool and an effective provider incentive program with the potential to improve childhood asthma management in marginalized populations.